VERSI SEKULARISME INDONESIA SEBAGAI KEBIJAKAN YANG DEMOKRATIS - Ambrosius Markus Loho; Karen Alfa Pontoan (Genta Hredaya: Media Informasi Ilmiah Jurusan Brahma Widya STAHN Mpu Kuturan Singaraja, 2022)
The fact of plurality in Indonesia is characterized by a religious diversity. This discussion paper is going to present the efforts to manage the tolerance of the inter-faith, including also how a precise trategy is related to the relationship between the religions and the state. Is the relationship between the religions and the state in Indonesia linked closely with any radical secularism such as in France or Indonesia that has a version of secularism itself? The writer will discuss the question by elaborating on the relationship between the religions and the state according to Pancasila. The type of secularism that is suitable and ideal for Indonesia is the one that nuances a separation of the religions and the state that is in the rigor version of liberal democracy, cannot be absolutely applied in Indonesia. The reason is that Indonesia has a wealth of culture that affecs the different way of view and reception against secularism. Even some thinkers argue that the acceptance of Indonesia against secularism can be one of the new examples/alternatives in which that the reception against secularism does not mean to be standing on the preconditions for a la western like democracy, liberalism, etc,. The issue is how to translate the values of cultural religious are to be matched with the values of the secular with the consideration that Indonesia still maintain the condition of ethnocentrism. Keywords: Secularism, Indonesia, plurality, Indonesia